Pengaruh Penyuluhan Metode Fast Terhadap Pengetahuan Perawat Dalam Deteksi Dini Penyakit Stroke Di Desa Taccorong Kabupaten Bulukumba - Haerati; Nurlina (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2020)
The understanding of stroke grievance, exactly in the high-risk category (hypertension, atrial fibrillation, and other vascular cases and diabetes) needed to be shared. To know and detect the stroke happen, we could use the F-A-S-T method. The aim of this research was to know the effect of FAST method observation on the nurses' understanding of detecting early stroke disease in Desa Binaan KabupatenBulukumba.The populations of this research were all the nurses in Desa Binaan KabupatenBulukumba with 30 people. The sample of this research used all the total populations. The sampling technique was total sampling. This research was quantitative research with the pre experimental research design. The type of the test used was the Wilcoxon test in which the result of the pre-test was 27 respondents (90.0%) nurses' understanding in the low-level category and 0 respondents (0.0%) in the fair level of understanding while in the post-test, there were 13 (43.3%) respondents with the fair level of understanding and 9 respondents (30,0%) with the good level of understanding. The conclusion of this research was there was the effect of FAST method observation toward the nurses' understanding in detecting early stroke disease in Desa Binaan Kabupaten Bulukumba The suggestion for this research was the findings of this research could be a reference and improve the students' understanding, added information and input for all the medical staff to improve the quality of health services and the further research was needed.